Current status of immunotherapy for non-small cell lung cancer - Yang, Tao; Xiong, Yilin; Zeng, Yufei; Wang, Yan; Zeng, Jing; Liu, Jie; Xu, Shangfu; Li, Li-Sheng (Frontiers in Pharmacology, 2022)
Nowadays, lung cancer is still the deadliest oncological disease in the world. Among them, non-small cell lung cancer (NSCLC) accounts for 80%∼85% of all lung cancers, and its 5-year survival rate is less than 15%, making the situation critical. In the past decades, despite some clinical advances in conventional treatments, the overall survival rate of NSCLC is still not optimistic due to its unique physiological conditions and the frequent occurrence of tumor escape. In recent years, immunotherapy has become a new hot spot in lung cancer research, including antibody therapy and cell therapy, which have been developed and utilized one after another, especially immune checkpoint inhibitor (ICI). These approaches have effectively improved the overall survival rate and objective response rate of NSCLC patients by enhancing the immune capacity of the body and targeting tumor cells more effectively, which is more specific and less toxic compared with conventional chemotherapy, and providing more strategies for NSCLC treatment. In this paper, we reviewed the relevant targets, clinical progress and adverse reaction in monoclonal antibodies, antibody-drug conjugates, ICI, bispecific antibodies, T-cell receptor engineered T cell therapy (TCR-T), Chimeric antigen receptor T-cell immunotherapy (CAR-T), and also report on their combination therapy from the immune-related background to provide better NSCLC treatment and prospective.